The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1111/odi.12103
|View full text |Cite
|
Sign up to set email alerts
|

Urban legends series: oral manifestations of HIV infection

Abstract: Human immunodeficiency virus-related oral lesions (HIV-OLs), such as oral candidiasis (OC) and oral hairy leukoplakia (OHL), have been recognized as indicators of immune suppression since the beginning of the global HIV epidemic. The diagnosis and management of HIV disease and spectrum of opportunistic infection has changed over the past 30 years as our understanding of the infection has evolved. We investigated the following controversial topics: (i) Are oral manifestations of HIV still relevant after the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(78 citation statements)
references
References 115 publications
(175 reference statements)
2
73
0
3
Order By: Relevance
“…Candida albicans is the dominating bacteria in oropharyngeal engraftment of region's HIV/ AIDS patients, which is consistent with what Balkhair, et al reported [8]. That is, there is a close relationship between engraftment of immune status and patients' immunity condition [9]- [11]. PSM mostly distributes in the circulatory system and joint, parts of it in the respiratory tract, enteron.…”
Section: Discussionsupporting
confidence: 76%
“…Candida albicans is the dominating bacteria in oropharyngeal engraftment of region's HIV/ AIDS patients, which is consistent with what Balkhair, et al reported [8]. That is, there is a close relationship between engraftment of immune status and patients' immunity condition [9]- [11]. PSM mostly distributes in the circulatory system and joint, parts of it in the respiratory tract, enteron.…”
Section: Discussionsupporting
confidence: 76%
“…This classification considers that the incidence of major and herpetiformis types are increased in patients with HIV infection [7]. For pediatric patients with HIV infection this classification is modified and recurrent aphthous stomatitis is in the group 1 (lesions commonly associated with pediatric HIV infection) [8].…”
Section: Discussionmentioning
confidence: 99%
“…They have been accepted as markers of immunosuppression (Miziara and Weber 2006 ;Reginald and Sivapathasundharam 2010 ;Patton et al, 2013 ), contributing for the early identifi cation of HIV infection or AIDS (Dias et al, 2012 ). In addition, OHL and OC can be a sign to warn dentists on the decreasing immunological condition of HIVinfected patients (Moura et al, 2006 ;Sontakke et al, 2011 ;Bodhade et al, 2011 ).…”
Section: Oral Candidiasis Oral Hairy Leukoplakia and Hiv Infectionmentioning
confidence: 99%
“…Moura et al ( 2010 ) observed that the treatment with podophyllin with acyclovir cream was more effective in the clinical healing rate for OHL than podophyllin and podophyllin with penciclovir cream, and no recurrent OHL was observed in this fi rst treatment. Additional studies have been conducted on the treatment for OHL with antiviral agents in topical creams (Patton et al, 2013 ).…”
Section: Ohl Treatmentmentioning
confidence: 99%